Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar Mata Pelajaran Ekonomi Kelas XI SMA Negeri 5 Pematang Siantar Tahun Ajaran 2023/2024 - Ilsa Dian Pika Saragih; Herlina Hotmadinar Sianipar; Tumpal Manahara Siahaan (JOURNAL SAINS STUDENT RESEARCH, 2023)
Education is the most important part that every human being must have, both formally and informally, to gain knowledge and learning experience. The development of science and technology has brought changes to almost all aspects of human life, including formal education. Education is a very important thing in life. The purpose of this research is to determine the effect of using Audio Visual Media on Learning Outcomes in Class XI Economics Subjects at SMA Negeri 5 Pematang Siantar. Academic Year 2023/2024. This research is quantitative. The measurement scale uses a Likert scale. In data analysis using manual multiple regression testing. Based on the calculation results, it shows that the price variable partially has an influence on learning outcomes, namely 80.232. This means that the better the learning media used, the higher the learning outcomes you will get